HUBUNGAN ANTARA EFIKASI DIRI DENGAN PROKRASTINASI AKADEMIK PADA SISWA KELAS XI SMA NEGERI 9 PADANG - Nelia - Afriyeni (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
This research is aimed to know the relationship between self-efficacy and academic procrastination toward students in second year at senior high school state 9 of Padang. Respondents that are used in the research are the students in second year at senior high school state 9 of Padang. The research is conducted to the 66 students in second year and in the academic year of 2008/2009, where the respondents' determination is done by random sampling technique. The technique of data collecting is used the Likert scale models. That is the scale of self-efficacy and The Procrastination Assesment Scale-Students (PASS) that is developed by Solomon and Rothblum (1994). The methode for analyzing data that is used for testing hyphotesis in the research is the correlation Product Moment (Pearson). Before conducting hyphotesis test, firts, it must done of using test assumptions by normality and linearity test. The result of data analysis shows efficacy scores are at a moderate scale (60,6%), and also the procrastination academic scores are at a moderate scale (72,73%). From the result of data processing is obtained p = 0,000 < 0,01 with a correlation coefficient -0,574 it means hyphotesis is accepted. The result shows there is a negative and significant relationship between self-efficacy and academic procrastination toward the students in the second year at senior high school state 9 of Padang, with the effective contribution of 33%. Thus, it can be concluded that if the higher self-efficacy, then the lower the students' academic procrastination behavior. Conversely, the lower of the self-efficacy, the higher the students' academic procrastination behavior